Recent Progress in Lithium Niobate - Jackson, Robert A.; Szaller, Zsuzsanna (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is a collection of research papers that describe some of the latest research on lithium niobate, which is an important material with many technological applications. The papers fall into three sections, which respectively consider the relationship between photorefractive properties and the defect structure of lithium niobate, powder preparation using a wet chemistry method and high-energy ball-milling technique, and finally the investigation of the domain structures, stability and conduction, and applications in waveguide devices.